2024
DOI: 10.5534/wjmh.220283
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight is Associated with Sperm DNA Fragmentation and Assisted Reproductive Technology Outcomes in Primary Infertile Men: Results of a Cross-Sectional Study

Abstract: Purpose To assess the relationship between clinical and semen characteristics and assisted reproductive technology (ART) outcomes with different birth weight (BW) categories in a cohort of infertile men. Materials and Methods Data from 1,063 infertile men were analyzed. Patients with BW ≤2,500, 2,500–4,000, and ≥4,000 g were considered as having low BW (LBW), normal BW (NBW), and high BW (HBW), respectively. Testicular volume (TV) was assessed with a Prader orchidometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A huge systematic review of 180,000 singletons born [10] and 60,210 multiple births [9] after ART showed an increased risk of pre-term birth, small gestational age, and low birth weight compared to naturally conceived children. In addition, altered foetal and prenatal development could determine immaturity in different organs and affect reproductive adult health, as shown by [47]. Other authors, however, did not find such a negative association [11,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A huge systematic review of 180,000 singletons born [10] and 60,210 multiple births [9] after ART showed an increased risk of pre-term birth, small gestational age, and low birth weight compared to naturally conceived children. In addition, altered foetal and prenatal development could determine immaturity in different organs and affect reproductive adult health, as shown by [47]. Other authors, however, did not find such a negative association [11,14,15].…”
Section: Discussionmentioning
confidence: 99%